EFEKTIVITAS MODEL PEMBELAJARAN PICTURE AND PINTURE DALAM MENULIS KARANGAN ARGUMENTASI SISWA KELAS IX MTS SWASTA ULUMUL QUR’AN - Nila Safina (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2020)
Abstract This study aims to determine the effectiveness of picture and picture learning models in writing essays of class IX students of Medan Ulumul Qur'an Public Private Class IX. The method used in this study is an experimental method that is the post-test only design group method. The instrument used to capture the assignment data is writing an argumentation essay. From the data processing results obtained the average experimental class was 78.09, while the average control class was 71.66. Thus the value of the experimental class is higher than the control class. After testing the hypothesis obtained = 23.81 at a significant level a = 5% from the distribution list t dk 40, then obtained = 2.021. If the price is compared with the apparent price> (23.81> 2.021), it can be stated that the null hypothesis (Ho) is rejected and the alternative hypothesis(Ha) is accepted. Based on data analysis, it can be concluded that the use of picture and picture learning models in writing argumentation essays is more effective than expository learning methods. Keywords: picture and picture learning model, writing, argument essay